(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2008)
In this paper is for the first time dated the inception of the Lower Jurassic marly sedimentation and the lower Toarcian black shales in the Tuscan Nappe, based on semiquantitative analysis of the calcareous nannofossils recovered from the Calcare selcifero di Limano/Calcari e marne a Posidonia transition and the lower part of this latter unit. The boundary between these formations lies within the nannofossil NJT5 Lotharingius hauffii Zone (uppermost Pliensbachian to lower Toarcian), the lower portion of the Calcari e marne a Posidonia ranges from the nannofossil NJT5 Lotharingius hauffii Zone to the NJT7 Discorhabus striatus Zone (middle Toarcian) and the organic-rich interval lies in the nannofossil NJT6 Carinolithus superbus Zone (lower Toarcian). Consequently, the changes from carbonate-dominated to marly-dominated sedimentation (NJT5 Zone) and the black shales accumulation (NJT6 Zone) in the Tuscan and Umbria-Marche basins are two coeval sedimentary events.